Stark Broadening of Co II Lines in Stellar Atmospheres - Zlatko Majlinger; Milan S. Dimitrijević; Vladimir A. Srećković (Data, 2020)
Data for Stark full widths at half maximum for 46 Co II multiplets were calculated using a modified semiempirical method. In order to show the applicability and usefulness of this set of data for research into white dwarf and A type star atmospheres, the obtained results were used to investigate the significance of the Stark broadening mechanism for Co II lines in the atmospheres of these objects. We examined the influence of surface gravity (log g), effective temperature and the wavelength of the spectral line on the importance of the inclusion of Stark broadening contribution in the profiles of the considered Co II spectral lines, for plasma conditions in atmospheric layers corresponding to different optical depths.